Tremella fuciformis Polysaccharides Inhibited Colonic Inflammation in Dextran Sulfate Sodium-Treated Mice via Foxp3+ T Cells, Gut Microbiota, and Bacterial Metabolites - Xu, Yingyin; Xie, Liyuan; Zhang, Zhiyuan; Zhang, Weiwei; Tang, Jie; He, Xiaolan; Zhou, Jie; Peng, Weihong (Frontiers in Immunology, 2021)
Tremella fuciformis is an edible medicinal mushroom, and its polysaccharide components have been found to confer various health benefits. This study identified the protective effects of polysaccharides of Tremella fuciformis (TPs) against dextran sulfate sodium (DSS)-induced colitis in mice. High dose of TPs (HTPs) could prevent the colon from shortening, reduce activity of colonic myeloperoxidase and serum diamine oxidase (DAO), decrease the concentration of D-lactate, and alleviate the colonic tissue damage in colitic mice. HTPs treatment stimulated Foxp3+T cells, promoted the production of anti-inflammatory cytokines whereas it reduced the production of pro-inflammatory and the portion of immunoglobulin A (IgA)-coated bacteria. 16S rRNA sequencing analysis found that TPs significantly increased gut community diversity, and restored the relative abundances of Lactobacillus, Odoribacter, Helicobacter, Ruminococcaceae, and Marinifilaceae. According to metabolomic analysis, HTPs induced specific microbial metabolites akin to that in normal mice. Tyrosine biosynthesis, tryptophan metabolism, and bile acid metabolism were influenced in the HTPs group compared with those in the DSS group. HTPs could alleviate DSS-induced colitis by immunoregulation and restored the gut microbiota and microbial metabolites. The results confirmed that HTPs have potential to be developed as a food supplement to ameliorate intestinal diseases.